An energy analysis of torrefaction for upgrading microalga residue as a solid fuel. (June 2015) - Chen, Wei-Hsin; Huang, Ming-Yueh; Chang, Jo-Shu; Chen, Chun-Yen; Lee, Wen-Jhy
Graphical abstract: Highlights: Energy utilization of microalga residue torrefaction is analyzed by examining contour maps. Optimal operation can be found to maximize the heating value of biomass and minimize solid yield. Relative energy efficiency (REE) is defined to identify the performance of energy utilization. The maximum REE along the contour line of energy yield always occurs at 300 °C. The energy efficiency under a given energy yield can be enlarged by a factor of at least 2.13. Abstract: The torrefaction characteristics and energy utilization of microalga Chlamydomonas sp. JSC4 ( C. sp. JSC4) residue under the combination of temperature and duration are studied by examining contour maps. The torrefaction temperature on the contour line of solid yield has a trend to linearly decrease with increasing duration. An index of relative energy efficiency (REE) is introduced to identify the performance of energy utilization for upgrading biomass. For a fixed energy yield, the optimal operation can be found to maximize the heating value of the biomass and minimize the solid yield. The energy utilization under the combination of a high temperature and a short duration is more efficient than that of a low temperature and a long duration. The maximum REE along the contour line of energy yield is always exhibited at the highest temperature (300 °C) where the energy efficiency can be enlarged by a factor of at least 2.36.